DETERMINASI PERTUMBUHAN EKONOMI DI TUJUH NEGARA ASEAN PERIODE TAHUN 1996-2013 - Desyana Eka Pramasty; Lydia Rosintan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
Economic growth is also one of the most important indicators in determining the standard of living of people in a country, because of an increase in the production capacity of an economy that is manifested in the form of national income. Economic growth is an indication of the success of economic development, measured by comparing, for example, for domestic size, Gross Domestic Product (GDP) in the current year with the previous year. This study aimed to analyze the factors that affect economic growth in seven ASEAN countries period from 1996-2013. This study use panel data analysis. The factors that affect economic growth in seven ASEAN countries, namely foreign debt, foreign direct investment, and the rate of inflation. Based on panel data analysis of the results showed that the foreign debt has negative effect and significant on economic growth, foreign direct investment has positive effect and significant on economic growth and inflation rate has negative effect and significant on economic growth in seven ASEAN countries period from 1996-2013.